Sylvain Maechler, Accounting for Nature: Risk, Uncertainty, and the Global Political Economy of the Ecological Crisis - Sylvain Maechler (Revue de la Régulation)
This thesis looks at the various ways in which accounting has been mobilized over the past four decades by a variety of international actors in order to face the global ecological crisis. This process is studied using qualitative data: observations, interviews, and documents. Based on a “global political economy of the ecological crisis” approach, the thesis suggests that this accounting enterprise is part of a broader attempt to make the ecological crisis a predictable object, whose consequences could be anticipated. Through a typology of three types of accounting and by exposing their tensions and inconsistencies, both material and discursive, the thesis shows the limits, not only theoretical but also practical, of such an undertaking.